A sensitive molecularly imprinted polymer based quartz crystal microbalance nanosensor for selective determination of lovastatin in red yeast rice. (15th October 2015) - Eren, Tanju; Atar, Necip; Yola, Mehmet Lütfi; Karimi-Maleh, Hassan
Highlights: We developed sensitive and simple quartz crystal microbalance nanosensor for detection of lovastatin. The non-modified and lovastatin-imprinted surfaces were characterized. The proposed method was validated according to the International Conference on Harmonisation guideline. The developed quartz crystal microbalance nanosensor was applied to red yeast rice. Abstract: Lovastatin (LOV) is a statin, used to lower cholesterol which has been found as a hypolipidemic agent in commercial red yeast rice. In present study, a sensitive molecular imprinted quartz crystal microbalance (QCM) sensor was prepared by fabricating a self-assembling monolayer formation of allylmercaptane on QCM chip surface for selective determination of lovastatin (LOV) in red yeast rice. To prepare molecular imprinted quartz crystal microbalance (QCM) nanosensor, LOV imprinted poly(2-hydroxyethyl methacrylate–methacryloylamidoaspartic acid) [p(HEMA–MAAsp)] nanofilm was attached on the modified gold surface of QCM chip. The non-modified and improved surfaces were characterized by using contact angle, atomic force microscopy (AFM) and Fourier transform infrared (FTIR) spectroscopy. The imprinted QCM sensor was validated according to the ICH guideline (International Conference on Harmonisation). The linearity range was obtained as 0.10–1.25 nM. The detection limit of the prepared material was calculated as 0.030 nM. The developed QCM nanosensor was successfully used to examine red yeast rice. Furthermore, the stability and repeatability of the prepared QCM nanosensor were studied. The spectacular long-term stability and repeatability of the prepared LOV-imprinted QCM nanosensor make them intriguing for use in QCM sensors.